THE CYTOPLASMIC RNA OF HELA CELLS: NEW DISCRETE SPECIES ASSOCIATED WITH MITOCHONDRIA - Vesco, Cesare (1969)
Two new species of cytoplasmic RNA with approximate sedimentation values of 12S and 21S, and which appear associated with mitochondria, are described. The species are unmethylated, are relatively metabolically stable, and have a 43 per cent G + C content. Their synthesis is uniquely resistant to inhibition by UV irradiation. The 12S and 21S RNA do not appear to be components of polysome-like structures.